Facilitation of Pain in the Human Spinal Cord by Nocebo Treatment - Geuter, Stephan (J Neurosci, 2013)
Nocebo hyperalgesia is an increase in subjective pain perception after a patient or subject underwent an inert treatment without any active ingredient. For example, verbal suggestion of increased pain can enhance both pain experience and responses in pain-related cortical brain areas. However, changes in cortical pain responses may be secondary to earlier amplification of incoming pain signals within the spinal cord. To test for a potential early enhancement of pain signals in the dorsal horn of the spinal cord, we combined a nocebo heat pain paradigm with spinal functional magnetic resonance imaging in healthy volunteers. We found that local application of an inert nocebo cream on the forearm increased pain ratings compared with a control cream, and also reduced pain thresholds on the nocebo-treated skin patch. On the neurobiological level, pain stimulation induced a strong activation in the spinal cord at the level of the stimulated dermatomes C5/C6. Comparing pain stimulation under nocebo to a control pain stimulation of the same physical intensity revealed enhanced pain-related activity in the ipsilateral dorsal horn of the spinal cord. Importantly, the activation of the main effect of pain and the nocebo effect spatially overlapped. The current study thus provides direct evidence for a pain-facilitating mechanism in the human spinal cord before cortical processing, which can be activated by cognitive manipulations such as nocebo treatments.